The New York state reporter (W.C. Little & Co., 1886)
"Containing all the current decisions of the courts of record of New York State, namely: Court of Appeals, Supreme Court, New York Superior Court, New York Common Pleas, Superior Court of Buffalo, City Court of New York, City Court of Brooklyn, and the Surrogates' Courts" (varies slightly)